Penerapan Model Internet Of Things Pada Pelaku UMKM Di Kabupaten Bekasi - Hamzah Muhamad Mardi Putra Putra; Arief Teguh Nugroho (Prosiding Sains dan Teknologi, 2022)
The development of Internet Technology in the business world and the industrial world took place very quickly in the modern and post-millennial era , namely after the 2000s. Technology has generally made our lives simpler and more practical with the term world in the palm of your hand just by mastering Technology and the Internet. . Several technological model innovations such as the Technology Acceptance Model (TAM) and technology readiness index (TRI), especially the development of social media technology for user, can help business development. The purpose of this study is to identify the use of technology and analyze the influence of technology and the internet on the use of social media on Micro, Small and Medium Enterprises in the District Bekasi. The output of this research is the implementation of IoT-based technology on Micro, Small and Medium Enterprises in Bekasi Regency. The application of technology and the Internet to Micro, Small and Medium Enterprises can provide convenience and usefulness when running a business in the era of globalization and modernization. In order to be a sustainable solution, this IoT-based technology model will be patented to make it easier for user to adopt technology so that socio-economic improvements occur. Keywords: IoT, Technology Acceptance Model, medium Entreprises